The Epidemic of Extended-Spectrum-β-Lactamase-Producing Escherichia coli ST131 Is Driven by a Single Highly Pathogenic Subclone, H30-Rx - Lance B. Price (American Society for Microbiology, 2013)
ABSTRACT The Escherichia coli sequence type 131 (ST131) clone is notorious for extraintestinal infections, fluoroquinolone resistance, and extended-spectrum beta-lactamase (ESBL) production, attributable to a CTX-M-15-encoding mobile element. Here, we applied pulsed-field gel electrophoresis (PFGE) and whole-genome sequencing to reconstruct the evolutionary history of the ST131 clone. PFGE-based cluster analyses suggested that both fluoroquinolone resistance and ESBL production had been acquired by multiple ST131 sublineages through independent genetic events. In contrast, the more robust whole-genome-sequence-based phylogenomic analysis revealed that fluoroquinolone resistance was confined almost entirely to a single, rapidly expanding ST131 subclone, designated H30-R. Strikingly, 91% of the CTX-M-15-producing isolates also belonged to a single, well-defined clade nested within H30-R, which was named H30-Rx due to its more extensive resistance. Despite its tight clonal relationship with H30Rx, the CTX-M-15 mobile element was inserted variably in plasmid and chromosomal locations within the H30-Rx genome. Screening of a large collection of recent clinical E. coli isolates both confirmed the global clonal expansion of H30-Rx and revealed its disproportionate association with sepsis (relative risk, 7.5; P < 0.001). Together, these results suggest that the high prevalence of CTX-M-15 production among ST131 isolates is due primarily to the expansion of a single, highly virulent subclone, H30-Rx. IMPORTANCE We applied an advanced genomic approach to study the recent evolutionary history of one of the most important Escherichia coli strains in circulation today. This strain, called sequence type 131 (ST131), causes multidrug-resistant bladder, kidney, and bloodstream infections around the world. The rising prevalence of antibiotic resistance in E. coli is making these infections more difficult to treat and is leading to increased mortality. Past studies suggested that many different ST131 strains gained resistance to extended-spectrum cephalosporins independently. In contrast, our research indicates that most extended-spectrum-cephalosporin-resistant ST131 strains belong to a single highly pathogenic subclone, called H30-Rx. The clonal nature of H30-Rx may provide opportunities for vaccine or transmission prevention-based control strategies, which could gain importance as H30-Rx and other extraintestinal pathogenic E. coli subclones become resistant to our best antibiotics.